Thermal, ferroelastic, and structural properties near phase transitions of organic–inorganic perovskite type [NH3(CH2)3NH3]CdBr4 crystals. Issue 29 (13th May 2021) - Lim, Ae Ran
Abstract : We studied the thermal behavior and structural dynamics of [NH3 (CH2 )3 NH3 ]CdBr4 near phase transition temperatures. Abstract : Hybrid perovskites have potential applications in several electrochemical devices such as supercapacitors, batteries, and fuel cells. Therefore, we studied the thermal behavior and structural dynamics of organic–inorganic hybrid perovskite [(NH3 )(CH2 )3 (NH3 )]CdBr4 crystals near phase transition temperatures, T C2 (=328 K) and T C1 (=363 K), which are correlated to the structural dynamics of cations and anions. The structural geometry and molecular dynamics with emphasis on the role of the [(NH3 )(CH2 )3 (NH3 )] cation and CdBr6 anion were discussed in terms of MAS 1 H NMR, MAS 13 C NMR, 14 N NMR, and 113 Cd NMR as a function of the temperature. The environments surrounding 1 H, 13 C, 14 N, and 113 Cd are investigated near T C1 and T C2 using these results. Spin–lattice relaxation times T 1ρ were discussed in terms of the change in temperature. The discontinuous changes of 1 H T 1ρ and 13 C T 1ρ near T C1 are consistent with the change of the lattice constant. Shorter T 1ρ values at high temperature indicate that 1 H and 13 C in the organic chains are more flexible at these temperatures. Based on these results, the physicochemical properties of the cation and anion during the III–II–I phase transitions were discussed. This study was conducted to improve the relatively weak thermal stability compared to the high efficiency for a variety of applications.